Plant perspectives to global climate changes : developing climate-resilient plants - Aftab, Tariq; Roychoudhury, Aryadeep (Elsevier, Academic Press, an Imprint of Elsevier, 2022)
Plant Perspectives to Global Climate Changes: Developing Climate-Resilient Plants reviews and integrates currently available information on the impact of the environment on functional and adaptive features of plants from the molecular, biochemical and physiological perspectives to the whole plant level. The book also provides a direction towards implementation of programs and practices that will enable sustainable production of crops resilient to climatic alterations. This book will be beneficial to academics and researchers working on stress physiology, stress proteins, genomics, proteomics, genetic engineering, and other fields of plant physiology. Advancing ecophysiological understanding and approaches to enhance plant responses to new environmental conditions is critical to developing meaningful high-throughput phenotyping tools and maintaining humankind's supply of goods and services as global climate change intensifies.